New species amongst Sri Lanka’s extinct shrub frogs (Amphibia: Rhacophoridae: Philautus) - Meegaskumbura, Madhava; Manamendra-Arachchi, Kelum; Schneider, Christopher J.; Pethiyagoda, Rohan (Zootaxa, 2007)
An extensive survey of amphibians in Sri Lanka, a 65,000 km2 continental island, has recently served to uncover ~100 new species of amphibians, mostly Oriental shrub-frogs of the endotrophic genus Philautus. Comparison of specimens acquired in the course of this survey with type and other historical collections have previously shown that 19 species have disappeared from the island. The final two extinct species, Philautus pardus and P. maia, known only from collections made in the island prior to 1876, are described herein as new. A contemporaneous account of the latter species reported that the female carried its clutch of eggs adhered to its belly, a behaviour which, if true, is unique in Anura. The remarkable extinction of anurans in Sri Lanka appears to be largely a result of the loss of c. 95 % of the island’s perhumid forests. Sri Lanka’s amphibian extinctions have been detectable only because of the baseline offered by specimens collected in the period 1850–1940 and preserved in overseas natural-history museums. Historical biodiversity collections in the world’s natural history museums thus offer outstanding value as baselines for contemporary biodiversity conservation assessments.